Theory and method in higher education research. Vol. 2 - Huisman, Jeroen; Tight, Malcolm (Bingley, U.K. : Emerald, 2016)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies is being applied. This volume of Theory and Method in Higher Education Research contains contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education. Amongst the theories discussed are actor-network theory, institutional logics, strategic positioning and threshold concepts. In terms of method and methodology, contributions consider validity in qualitative research, measuring competences, international-comparative research, shadowing, participatory research and participant-centred approaches to interviewing.
The old questions are the best: striving against invalidity in qualitative research / Betina Da Silva Lopes, Helena Pedrosa-De-Jesus, Mike Watts -- Using grounded theory to discover threshold concepts in transformative learning experiences / Virginia M. Tucker, Christine Bruce, Sylvia L. Edwards -- Methods for assessing competences in higher education: a comparative review / Edith Braun, Shweta Mishra -- The academic home of higher education research: the case of doctoral theses in Sweden / Eva Forsberg, Lars Geschwind -- Constructing future visions about higher education with participatory methods / Ga<U+0301>bor Kira<U+0301>ly, Zsuzsanna Ge<U+0301>ring, Alexandra Ko<U+0308>ves, Sa<U+0301>ra Csillag, Gergely Kova<U+0301>ts -- Connecting theory and practice in qualitative research / Carolina Guzma<U+0301>n-Valenzuela -- Studying higher education close-up: unexplored potentials of 'shadowing' in higher education research / Meta Gorup -- Developing a participant-centred approach to qualitative research interviewing / Marjorie McCrory, Victoria O'Donnell -- Co-creating higher education reform with actor-network theory: experiences from involving a variety of actors in the processes of knowledge creation / Laura Sarauw -- The precision and rigor of international comparative studies in higher education / Anna Kosmu<U+0308>tzky -- Strategic positioning in higher education: reshaping perspectives / Marian Mahat, Leo Goedegebuure -- Universities as hybrids: applications of institutional logics theory to higher education / Benedetto Lepori.
Includes bibliographical references.
Print version record
Keywords: Education -- Higher; Higher & further education, tertiary education; Education, Higher -- Research